Early results from a single centre's experience with the STRYDE nail: a cause for concern?. (1st June 2021) - Iliadis, Alexios Dimitrios; Wright, Jonathan; Stoddart, Michael Thomas; Goodier, William David; Calder, Peter
Abstract : Aims: The STRYDE nail is an evolution of the PRECICE Intramedullary Limb Lengthening System, with unique features regarding its composition. It is designed for load bearing throughout treatment in order to improve patient experience and outcomes and allow for simultaneous bilateral lower limb lengthening. The literature published to date is limited regarding outcomes and potential problems. We report on our early experience and raise awareness for the potential of adverse effects from this device. Methods: This is a retrospective review of prospective data collected on all patients treated in our institution using this implant. We report the demographics, nail accuracy, reliability, consolidation index, and cases where concerning clinical and radiological findings were encountered. There were 14 STRYDE nails implanted in nine patients (three male and six female) between June 2019 and September 2020. Mean age at surgery was 33 years (14 to 65). Five patients underwent bilateral lengthening (two femoral and three tibial) and four patients unilateral femoral lengthening for multiple aetiologies. Results: At the time of reporting, eight patients (13 implants) had completed lengthening. Osteolysis and periosteal reaction at the junction of the telescopic nail was evident in nine implants. Five patients experienced localized pain and swelling. Macroscopic appearances following retrieval were consistent with corrosion at the telescopic junction. Tissue histology was consistent with effects of focal metallic wear debris. Conclusion: From our early experience with this implant we have found the process of lengthening to be accurate and reliable with good regenerate formation and consolidation. Proposed advantages of early load bearing and the ability for bilateral lengthening are promising. We have, however, encountered concerning clinical and radiological findings in several patients. We have elected to discontinue its use to allow further investigation into the retrieved implants and patient outcomes from users internationally. Cite this article: Bone Joint J 2021;103-B(6):1168–1172.